2014
DOI: 10.1111/ijfs.12644
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological, physical and chemical characteristics of freshwater prawns (Macrobrachium rosenbergii) in modified‐atmosphere packaging

Abstract: Summary This study evaluated the influence of packaging atmosphere (air versus 50% N2/50% CO2) on microbiological (mesophiles, psychrotrophs), physical (gas measurement) and chemical (pH, total volatile basic nitrogen [TVB‐N], NH3, H2S and biogenic amines) parameters in freshwater prawns during storage at 0 ± 1 °C for 240 h. To select the most appropriate packaging, 21 batches of each treatment were analysed. Both the packaging permeability and the combination of gases affected the shelf life, but the modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Our results revealed that both O 2 /CO 2 enriched atmospheres and vacuum packaging reduced the growth of spoilage bacteria, probably due to the antibacterial activity of CO 2 and the high levels or absence of O 2 [30,33,37]. In agreement with our findings, some authors have already reported that MAP with different O 2 and CO 2 ratios and vacuum packaging can delay the formation of TVB-N by decreasing the growth rate of spoilage bacteria in refrigerated meat [36,38].…”
Section: Physicochemical Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results revealed that both O 2 /CO 2 enriched atmospheres and vacuum packaging reduced the growth of spoilage bacteria, probably due to the antibacterial activity of CO 2 and the high levels or absence of O 2 [30,33,37]. In agreement with our findings, some authors have already reported that MAP with different O 2 and CO 2 ratios and vacuum packaging can delay the formation of TVB-N by decreasing the growth rate of spoilage bacteria in refrigerated meat [36,38].…”
Section: Physicochemical Parameterssupporting
confidence: 91%
“…The increase in the pH value for AA might be attributed to the accumulation of basic compounds derived from the growth of Pseudomonas spp. and associated sub-species [30]. The decrease of the pH value in 10-50% CO 2 MAP treatments may be attributed to the formation of carbonic acid by the dissolution of CO 2 in water [31].…”
Section: Physicochemical Parametersmentioning
confidence: 95%
“…can be controlled by as little as 5% CO 2 [ 131 ]. The reduction of total viable counts as a result of including CO 2 in the gas mix has been further confirmed in many of the studies in this review encompassing the following species/products listed in Table 1 : bonito [ 72 ], cod [ 6 , 21 , 22 , 30 , 76 ], crayfish [ 79 ], halibut [ 81 ], lingcod [ 82 ], mussels [ 87 ], mullet [ 85 ], prawn [ 88 ], salmon [ 25 ], sardines [ 32 ], scallops [ 93 ], sea bass [ 26 , 96 , 112 ], seabream [ 19 , 95 ], shrimp [ 31 , 100 , 103 , 113 , 114 , 116 ], squid [ 118 ], tilapia [ 28 ], and trout [ 119 , 120 , 123 ].…”
Section: Microbiological Considerationsmentioning
confidence: 60%
“…Total Volatile Basic Nitrogen (TVB-N) is a chemical indicator often used to determine freshness of fish and fishery products held on ice. Determination of TVB-N values and Trimethylamine (TMA) content are widely used in shelf life studies of MAP seafood [ 6 , 25 , 32 , 38 , 88 , 99 , 123 ]. Some authors determined a correlation between quality deterioration of MAP seafood and increased TVB-N or TMA values, but often noted the levels were below limit for consumption at the end of the product shelf life [ 32 , 123 ].…”
Section: Physicochemical and Organoleptic Considerationsmentioning
confidence: 99%
“…By chilling the fish, some of the bacteria groups responsible for the spoilage will halt to grow, and the rate of spoilage will thereby be reduced (Himelbloom et al ., ; Kim et al ., ). The vacuum‐packaging reduces oxidation and the growth of aerobic microorganisms and thereby increases the shelf life of fish (Kumar & Ganguly, ; Simoes et al ., ). In addition, the packaging of foods prior to radiation treatment is necessary to prevent microbial contamination during postirradiation storage.…”
Section: Introductionmentioning
confidence: 97%